Brain volume is a better biomarker of outcomes in ischemic stroke compared to brain atrophy - Alhadid, Kenda; Regenhardt, Robert W.; Rost, Natalia S.; Schirmer, Markus D. (Frontiers in Stroke, 2024)
Objective: To assess if brain volume at the time of ischemic stroke injury is a better biomarker of functional outcome than brain atrophy.Background: Brain parenchymal fraction (BPF) has been used as a surrogate measure of global brain atrophy, and as a neuroimaging biomarker of brain reserve in studies evaluating clinical outcomes after brain injury. Brain volume itself is affected by natural aging, cardiovascular risk factors, and biological sex amongst other factors. Recent works have shown that brain volume at the time of injury can influence functional outcomes, where larger brain volumes are associated with better outcomes.Methods: Acute ischemic stroke cases at a single center between 2003 and 2011, with neuroimaging obtained within 48 hours from presentation were eligible. Functional outcomes represented by the modified Rankin Score (mRS) at 90 days post admission (mRS≤2 deemed a favorable outcome) were obtained via patient interview or per chart review. Deep learning enabled automated segmentation pipelines were used to calculate brain volume, intracranial volume (ICV), and BPF on the acute neuroimaging data. Patient outcomes were modeled through logistic regressions, and model comparison was conducted using the Bayes Information Criterion (BIC).Results: 467 patients with arterial ischemic stroke were included in the analysis, median age was 65.8 years, and 65.3% were male. In both models, age and a larger stroke lesion volume were associated with worse functional outcomes. Higher BPF and a larger brain volume were both associated with favorable functional outcomes, however, comparison of both models suggested that the brain volume model (BIC=501) better explains the data compared to the BPF model (BIC=511).The extent of global brain atrophy (and its surrogate biomarker BPF) has been regarded as an important biomarker of functional post-stroke outcomes and resilience to acute injury. Here we demonstrate that a higher global brain volume at time of injury better explains favorable functional outcomes, which can be directly measured in a clinical setting